Silver people : voices from the Panama Canal - Engle, Margarita (Houghton Mifflin Harcourt, 2014)
Fourteen-year-old Mateo and other Caribbean islanders face discrimination, segregation, and harsh working conditions when American recruiters lure them to the Panamanian rain forest in 1906 to build the great canal.